Development and Validation of an Ion-Pair HPLC-UV Method for the Quantitation of Quinoline and Indoloquinoline Alkaloids in Herbal and Pharmaceutical Antimalarial Formulations - Samuel Oppong Bekoe; Emmanuel Orman; Samuel Awenteka Adjabui; Abena Amponsaa Brobbey; James Oppong-Kyekyeku; Kwabena Frimpong-Manso Opuni; Noble Kuntworbe; Samuel Asare-Nkansah (Journal of Chemistry)
Quinine- and cryptolepine-based antimalarials serve as valuable alternatives to artemisinin-based combination therapies (ACTs) in Ghana. Their use, however, is associated with adulteration and substandard quality challenges. An HPLC method targeting quinoline and indoloquinoline antimalarial alkaloids was developed, validated, and applied to evaluate herbal and pharmaceutical antimalarial formulations (HPAFs) and starting materials (APIs). The separation/quantitation of the alkaloids (including quinine, quinidine, cinchonine, cinchonidine, dihydroquinine, dihydroquinidine, and cryptolepine) was achieved on a Zorbax SB-CN column (250 mm × 4.6 mm, 5 μm), with an isocratic elution system of methanol: trifluoroacetic acid (0.1%, v/v) (15 : 85, v/v) at 1.5 mL/min and 223 nm. Method validation was according to ICH Q2(R1) guidelines. It was then used to assess the quality of APIs (n = 3) and HPAFs (n = 44) including quinine-based pharmaceutical antimalarial formulations (QBPAFs) (n = 23) and herbal antimalarial products (HAMPs). The method was found to be specific, selective, accurate, precise, and robust toward the alkaloids with linearity achieved within specified concentration ranges (r2 > 0.995 for all analytes). Analyte stability ranged between 6 and 12 hours. All the APIs contained quinine <99.0%–101.0%, with dihydroquinine and cinchonidine at levels compliant with the established acceptance criteria. The QBPAFs had quinine content ranging between 50.2% and 151.2%, with 43.5% (n = 10/23) of them complying with the acceptance criteria. The related alkaloids observed in the QBPAFs included quinidine (56.5%, n = 13/23), dihydroquinine (100%, n = 23/23), dihydroquinidine (21.7%, n = 5/23), cinchonine (17.4%, n = 4/23), and cinchonidine (95.7%, n = 22/23). For the HAMPs, 81.0% (n = 17/21) were adulterated with quinine (0.59 ± 0.04 mg/10 mL–86.03 ± 0.02 mg/10 mL). Cryptolepine was identified in 19% (n = 4/21) of the HAMPs with concentration ranging between 43.99 ± 0.43 μg/mL and 747.86 ± 0.34 μg/mL. In conclusion, the application of the ion-pair HPLC method targeting quinoline and indoloquinoline antimalarials has demonstrated the presence of quality and poor-quality HPAFs on the Ghanaian market.